2014
DOI: 10.1371/journal.pone.0086085
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Rensch’s Rule in Greater Horseshoe Bat (Rhinolophus ferrumequinum) with Female-Biased Sexual Size Dimorphism

Abstract: Sexual size dimorphism (SSD) is widespread within the animal kingdom. Rensch’s rule describes a relationship between SSD and body size: SSD increases with body size when males are the larger sex, and decreases with body size when females are the larger sex. Rensch’s rule is well supported for taxa that exhibit male-biased SSD but patterns of allometry among taxa with female-biased size dimorphism are mixed, there is evidence both for and against the rule. Furthermore, most studies have investigated Rensch’s ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 52 publications
2
38
2
Order By: Relevance
“…Although Rensch (1950) formulated his pattern as a seemingly interspecific trend, it is interesting that it has been often verified at the intraspecific level in groups where higher taxonomic units are not consistent with the rule. This was observed in the Greater Horseshoe bat (Rhinolophus ferrumequinum) (Wu et al, 2014), Panthera tigris subspecies (Martinez et al, 2014), domestic dog, cattle, and chicken (Polák and Frynta, 2010;Remeš and Székely, 2010;Frynta et al, 2012), and a melanopline grasshopper (Bidau and Martí, 2008a,b). As shown here and in Bidau and Medina (2013) at least one tuco-tuco species follows Rensch's rule intraspecifically although the other one tested (C. talarum), does not at least for the analysed trait.…”
Section: Discussionmentioning
confidence: 90%
“…Although Rensch (1950) formulated his pattern as a seemingly interspecific trend, it is interesting that it has been often verified at the intraspecific level in groups where higher taxonomic units are not consistent with the rule. This was observed in the Greater Horseshoe bat (Rhinolophus ferrumequinum) (Wu et al, 2014), Panthera tigris subspecies (Martinez et al, 2014), domestic dog, cattle, and chicken (Polák and Frynta, 2010;Remeš and Székely, 2010;Frynta et al, 2012), and a melanopline grasshopper (Bidau and Martí, 2008a,b). As shown here and in Bidau and Medina (2013) at least one tuco-tuco species follows Rensch's rule intraspecifically although the other one tested (C. talarum), does not at least for the analysed trait.…”
Section: Discussionmentioning
confidence: 90%
“…And finally, according to Wu et al (2014), skeletal measurements, such as forearm length as a proxy for body size, were more reliable than using body mass. First, we found that most studies dealing with variation in sexual size dimorphism in mammals used data collected from literature.…”
Section: Data Collectionmentioning
confidence: 99%
“…Males and females may respond differently to changes in temperature, and the degree of SSD can change substantially (Blanckenhorn and Demont 2004;Clauss et al 2013). Blanckenhorn and Demont 2004;Clauss et al 2013), studies investigating intraspecific variation in SSD trends are lacking Wu et al 2014). More recently, variations in SSD among populations within species were described (Kraushaar and Blanckenhorn 2002;Teder and Tammaru 2005), and in these cases, intraspecific changes in SSD may also occur due to sex differences in body size plasticity (Fairbairn 2005;.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations